KECERNAAN IN VITRO BISCUIT RANSUM KOMPLIT BERBAHAN PEREKAT EMPULUR SAGU (Metroxylon sagu) - Shirley Fredriksz; Lily Joris (JURNAL HUTAN PULAU-PULAU KECIL, 2020)
The objective of the study was to determine in-vitro digestibility of complete ration biscuit using sago pith as adhesive substance. The experiment was arranged in Complete Randomized Design with 5 treatments and 5 replications. The treatments were P1 (50% mini elephant grass+ 20% leucaena + 30% sago pith + 0% rice bran), P2 (50% mini elephant grass+ 20% leucaena + 25% sago pith + 5% rice bran), P3 (50% mini elephant grass+ 20% leucaena + 20% sago pith +10% rice bran ) and P4 (50% mini elephant grass+ 20% leucaena + 15% sago pith + 15% rice bran). Variables measured were digestibility of dry (DM) and organic matter (OM), NH3 level, total volatile fatty acid (VFA), and rumen pH. The results show that the treatment has no significant effect on vitro digestibility of dry and organic matter. In vitro -digestibility is ranging from 90.7 – 91.4% and 87.5 – 88.4 % for DM and OM, respectively. In-vitro test on complete ration biscuit which consists of sago pith, rice bran, mini elephant grass and leucaena leucocephala has no significant (P>0.05) on NH3 level, total volatile fatty acid and rumen pH. In conclusion, sago pith can be potentially used as adhesive substance in formulating complete ration biscuit.